Medicine, Magic and Art in Early Modern Norway Conceptualizing Knowledge - Ohrvik, Ane (Palgrave Historical Studies in Witchcraft and Magic, 2018)
This book addresses magical ideas and practices in early modern Norway. It examines a large corpus of Norwegian manuscripts from 1650-1850 commonly called Black Books which contained a mixture of recipes on medicine, magic, and art. Ane Ohrvik assesses the Black Books from the vantage point of those who wrote the manuscripts and thus offers an original study of how early modern magical practitioners presented their ideas and saw their practices. The book show how the writers viewed magic and medicine both as practical and sacred art and as knowledge worth protecting through encoding the text. The study of the Black Books illuminates how ordinary people in Norway conceptualized magic as valuable and useful knowledge worth of collecting and saving despite the ongoing witchcraft prosecutions targeting the very same ideas and practices as the books promoted. Medicine, Magic and Art in Early Modern Norway is essential for those looking to advance their studies in magical beliefs and practices in early modern Europe as well as those interested in witchcraft studies, book history, and the history of knowledge.